EXPLORING SYNTACTIC FLAWS IN STUDENTS' ARGUMENTATIVE WRITING: AN ERROR-DRIVEN APPROACH - Sri Widyarti Ali; Indri Wirahmi Bay, Nurfadiyah Palilati (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Writing well-formed sentences requires a strong grasp of grammar and vocabulary, which can be especially challenging for students when the target language differs significantly from their native language. When learning how words connect to form larger grammatical units, students often become confused about parts of speech, leading to errors. This study aimed to describe the syntactical errors found in 15 argumentative essays by fourth-semester English majors and identify the error sources through a descriptive qualitative method. The analysis revealed 47 syntactical errors across 5 categories: noun phrases with determiners (26 instances), conjunctions (6), numbers (5), auxiliary verbs (6), and prepositions (4). Both interlingual (native language influence) and intralingual (target language itself) factors contributed to these errors. Ultimately, this research hopes to raise awareness among students about producing grammatically correct written English.